Percutaneous transgluteal drainage (Revista Argentina de Cirugía, 2021)
Background: Percutaneous drainage is an alternative to surgery in the management of pelvic abscesses. The aim of this study is to evaluate the safety and efficacy of the transgluteal approach.Material and methods: Transgluteal percutaneous drainages were performed by 3 surgeons using computed tomography guidance. The Seldinger technique was used with 8 Fr and 10 Fr catheters under local anesthesia. Drainage was considered successful if the abscess regressed and did not recur.Results: Mean age was 49.2 years. Escherichia coli was the most common microorganism identified. In 50% of the cases, the abscesses occurred postoperatively. Mean duration of drainage was 9.2 days. Drainage was successful in all the cases and there were no major complications.Conclusion: Transgluteal computed tomography-guided approach is safe and well-tolerated for the treatment of deep pelvic abscesses.
Keywords: pelvic abscesses; transgluteal drainage; CT; infrapiriform